Precision foraging: Bats in organic desert palm plantations hunt where it is most needed - Danilo Russo; Fabiana Soprano; Luca Cistrone; Adi Einav; Jessica Schäckermann; Ioannis Ekklisiarchos; Carmi Korine (Global Ecology and Conservation)
Bats are crucial in suppressing pest arthropods in agroecosystems, contributing vitally to sustainable agriculture. However, the importance of bats in agriculture in extreme environments, such as deserts, has received far less attention. Date palm plantations represent one of the few productive systems in hyper-arid regions. We studied habitat use in an organic date palm plantation in the Arava Valley (Southern Israel) employing acoustic surveys to assess bat activity and foraging behaviour. According to our predictions, bats preferentially foraged in the plantation’s most productive areas, with most of the 13 recorded species exhibiting significant activity in older, sheltered plots. Higher wind speeds correlated with decreased foraging across most species, but sheltered habitats often buffered this effect. While species richness remained stable across habitats, according to our prediction, activity levels varied according to habitat type and wind conditions. In general, bat activity increased in old productive plots in the plantation’s core section and decreased elsewhere in response to strong winds. These results highlight the importance of maintaining older productive areas within the interiors of date palm plantations to support bat populations and enhance their pest-suppressing roles. Management strategies should design wind-buffering plantations to protect critical bat foraging areas and provide water sources. As date palm plantations act as ''oases'' in unproductive landscapes, many bats likely travel significant distances to forage there. Protecting bat habitats on a large scale and prioritising multiscale conservation is crucial to preserving bats and their ecosystem services.